The Rewilding Cinderella Project: Exploring the Ecological Multiplicities of the Cinderella Cycle. - Gilar, Joanna (Marvels & Tales, 2024)
The article explores the Rewilding Cinderella project, which seeks to highlight the ecological and relational complexities of the Cinderella narrative cycle across different global versions. Topics discussed include the project's approach to ecocritical storytelling, the challenges of naming and categorizing the diverse Cinderella tales, and the project's effort to widen participation in storytelling to reflect contemporary United Kingdom diversity.